A congenital cystic pulmonary airway malformation occurring together with both an extralobar pulmonary sequestration and an esophageal duplication cyst. Issue 1 (30th September 2019) - Dewberry, Lindel C.; Trecartin, Andrew; Galambos, Csaba; Hilton, Sarah A.; Dannull, Kimberly; Zaretsky, Michael V.; Behrendt, Nicholas; Galan, Henry L.; Marwan, Ahmed I.; Liechty, Kenneth W.
Abstract: A foregut duplication cyst occurring together with both a congenital cystic pulmonary airway malformation and extralobar pulmonary sequestration is an unusual combination. Prenatal ultrasound, MRI, and postnatal CT are helpful for operative planning. Surgical resection is the definitive management for all three anomalies. Abstract : A foregut duplication cyst occurring together with both a congenital cystic pulmonary airway malformation and extralobar pulmonary sequestration is an unusual combination. Prenatal ultrasound, MRI, and postnatal CT are helpful for operative planning. Surgical resection is the definitive management for all three anomalies.